Analisis Spasial Not in Employment, Education, or Training (NEET) di Indonesia Tahun 2021 - Simanjuntak, Moreno Kay Boy; Pasaribu, Ernawati (Seminar Nasional Official Statistics, 2023)
The role of the young population is crucial in maximizing the demographic bonus. It is necessary to pay attention to the education and employment absorption of young people. The NEET indicator can be used to asses the youth situation. In 2021, Indonesia's NEET rate was 22.4 percent, higher than most Southeast Asian countries. Most NEET studies primarily focus on individual characteristics, but NEET can also be influenced by spatial effects. This study aims to obtain an overview, identify spatial effects, and analyse the determinants of the NEET rate in Indonesia using the spatial durbin error model (SDEM). The findings reveal that the NEET rate is directly influenced by employment opportunities, net secondary school enrollment rate, percentage of people with disabilities, percentage of in-migrants, and the human development index. Additionally, the NEET rate is indirectly influenced by employment opportunities, the percentage of young married women, and the percentage of in-migrants.